Automatic Nutrient Control System Base on Internet of Things for Hydroponics Crops: https://doi.org/10.69692/SUJMRD0802331 - Bounnady, Khampheth; Thepphasolath, Soukvilay; Chanthaminavong, Senglathsamy; Louangvilay, Xaythavy (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
The objectives of this research are to examine the growth rate of plants, the yield, and the nutrient application rate. The research team has developed an automatic nutrient control system which consisted of an Arduino MEGA 2560 R3 as the main processor to receive data from the sensor, such as pH sensor as the sensor to measure the acidity, EC sensor as the sensor used to measure the internal current of a liquid. The Arduino MEGA 2560 R3 will transfer the signal to control the opening and closing of the pump of each nutrient to get the nutrient solution as determined; in addition, the data is send to the cloud via a NodeMCU ESP8266 board connected to the Arduino MEGA 2560 R3, which users can track the data through the application. In the experiment, the developed system was used to grow hydroponic lettuce in a greenhouse and compared to growing hydroponic lettuce by human care under the same environment. The result from experiments revealed that the proposed system can maintain the pH and EC values more stable than the cultivation of hydroponic lettuce by human care, and the growth rate was 99.04%, while the use of caregivers was 95.38%; its harvest of yields was more compared to the use of caregivers up to 7.35%, and the nutrient application rate was less than the care of caregivers at 22.05%.